2012
DOI: 10.1209/0295-5075/97/24004
|View full text |Cite
|
Sign up to set email alerts
|

Bubble puzzles in liquid squeeze: Cavitation during compression

Abstract: We let a steel ball fall on a thin liquid layer. Thereby the liquid was squeezed out from between the falling sphere and the solid boundary, which was made of thick glass, allowing for direct high-speed visualisation of the liquid layer at the point of closest approach. Surprisingly, vapour cavities were created during squeeze, with the liquid forced to change phase to vapour as the sphere approached the boundary and the pressure thus increased. This is a direct contradiction to common preconceptions, where cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Estimates of the tensile stress for onset of cavitation compared well to the maximum tension criterion proposed by Joseph [3]. Seddon et al [4] observed vapour cavities using high-speed imaging during approach of a steel ball onto a liquid covered glass plate. Uddin et al [5] also used high-speed imaging, and particle tracking, to investigate squeeze flow around a sphere impacting a non-Newtonian film covered plate.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Estimates of the tensile stress for onset of cavitation compared well to the maximum tension criterion proposed by Joseph [3]. Seddon et al [4] observed vapour cavities using high-speed imaging during approach of a steel ball onto a liquid covered glass plate. Uddin et al [5] also used high-speed imaging, and particle tracking, to investigate squeeze flow around a sphere impacting a non-Newtonian film covered plate.…”
Section: Introductionmentioning
confidence: 80%
“…High shear regions led to significant viscosity reduction which may have increased sphere penetration into the film and induced cavitation on sphere rebound. Mansoor et al [6] investigated dropping a tungsten carbide sphere onto a liquid covered glass surface, but were not able to reproduce results of Seddon et al [4] of cavitation forming before impact. In nature, cavitation occurs after impact of the raptorial appendage of a peacock mantis shrimp (Odontodactylus scyllarus), which can generate forces up to 1501 N at peak speeds of 14-23 m/s, aiding the shrimp's attack on its prey.…”
Section: Introductionmentioning
confidence: 93%
“…For all three release heights, the primary (white arrows) and secondary bubbles squeeze radially outwards as the sphere approaches towards the glass wall to create an annular bubble structure, which has previously been misinterpreted as shear-induced cavitation by Seddon et al (2012). While the deceleration of the sphere upon contact for h r = 47 mm is not enough for the liquid to open from these bubbles, an annular pattern of small bubbles connected in a foam-like structure is clearly seen for h r = 147 mm.…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…However, since the qualitative results provided therein suffered from a relatively low spatial and temporal resolution, further investigation was conducted by Mansoor et al (2014) using a synchronized dual-view (side and bottom) high-speed imaging system for similar experimental parameters. The results clarified that the annular bubble structure misinterpreted by Seddon et al (2012) as cavitation was in reality created by the entrapment of bubbles (Marston, Vakarelski & Thoroddsen 2011a) on the sphere surface as it entered into the viscous film, which subsequently squeezed radially outwards from the sphere centre as it approached the wall. Cavitation was only observed once the sphere made wall contact and started to rebound (e.g.…”
mentioning
confidence: 84%
See 1 more Smart Citation